2013
DOI: 10.3126/jcmc.v3i2.8435
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Care Practices in Hilly Area of Eastern Region of Nepal

Abstract: Antenatal care is provided during pregnancy to save lives of mother and foetus. The World Health Organization recommends four focused visits as sufficient for normal pregnancy. The objective of this study was to find out the antenatal care practices and its impact on birth outcome.The cross-sectional study was conducted from 28th March to 10th April, 2013 among the residents of Dhankuta municipality where 246 households were taken as subjects. Convenient purposive sampling technique was applied. Semi-structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…However, there was no linear increase in adjusted odds ratio as the wealth status increased from poorer to richer. Study in line with this result from Nepal indicated that women living in the richest circumstance visit ANC much more frequently than those in the poorest [16] also studies from Ethiopia [17,18], Kenya [19] support this result. This might be due to access to financial resources that could have enabled women to attend antenatal services frequently.…”
Section: Discussionsupporting
confidence: 67%
“…However, there was no linear increase in adjusted odds ratio as the wealth status increased from poorer to richer. Study in line with this result from Nepal indicated that women living in the richest circumstance visit ANC much more frequently than those in the poorest [16] also studies from Ethiopia [17,18], Kenya [19] support this result. This might be due to access to financial resources that could have enabled women to attend antenatal services frequently.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, 90% of the pregnant women took Albendazole tablet during pregnancy in this study. Similar study shows that 57.7% of pregnant women had taken Albendazole tablet during pregnancy 21 .Walking distance to the health facility and transportation availability is an important factor for the accessibility of health services.…”
Section: Discussionmentioning
confidence: 53%
“…Although there has been little meticulous evaluation of optimal timing of the initiation of ANC, pregnant women who receive late or no ANC are more likely to have poor or unfavorable outcomes of pregnancy. [4][5][6] Late initiation of ANC was reported as a significant risk factor for maternal mortality in some studies. [7][8][9] Therefore, ANC should begin as early as possible either at hospital/health center or during domiciliary visit of health workers in order to have sufficient time to manage risk factors, if present or to perform appropriate screening for early and timely referral.…”
Section: Introductionmentioning
confidence: 99%